The demand for mobile phone providers: case research on 5 mobile phone providers in Kuching Digi, Tm Touch, Maxis, Celcom & Timecel - Wong, Jason Tee Hock (Universiti Malaysia Sarawak (UNIMAS), 2003)
The study area includes five mobile phone providers that are situated in the middle of Kuching city. The recent boom and growth of mobile phone providers have seen an increase in the demand for mobile phone usage. The aim of this study is to examine the demand factors of the mobile phone providers. Factors such as advertisement, network coverage, rates, customer service and service package will be examined. In addition, consumers' understanding of the service offered by each mobile phone providers will be revealed. In doing this study, a sample of 300 consumers is chosen by using simple random sampling and questionnaires are distributed to them in order to get the data. The result of the study has revealed that more than 79.3% of, consumers in Kuching are satisfied with the service provided by mobile phone providers. The study found that factors such as advertisement, customer service, rates and service package have positive but weak relationship with the demand. However, interestingly the study found that network coverage has negative relationship. Even though most of the services provided by mobile phone providers are perceived to be good by customers but there are still many areas for improvement. Lastly, this paper has proposed some suggestions for the owner of mobile phone providers, as well as for future researchers as reference.